Constructive Deviance, Destructive Deviance and Personality: How do they interrelate? - Moran Bodankin; Aharon Tziner (Amfiteatru Economic Journal, 2009)
In recent years deviant behavior in organizations has drawn increasing attention. However, surprisingly little research has focused on constructive rather than destructive deviance. In an attempt to bridge this gap, the present study investigated both constructive and destructive deviance at work and their relationship to employee personality. Using 89 hitech employees, constructive and destructive (interpersonal and organizational) deviance were regressed on the big-five factors of personality. Findings show that neuroticism and agreeableness were related to both types of constructive deviance, whereas conscientiousness was associated with both types of destructive deviance. Moreover, agreeableness was connected to interpersonal destructive deviance, whereas openness to experience was connected to organizational constructive deviance. Theoretical and practical implications are suggested as well as a course for future research.
Keywords: D23; 330; work deviance; organizational misbehavior; personality and counterproductive behavior